El cine negro español: del spanish noir al policiaco actual [Reseña] - Daniel Maldonado-Casas (Revista Mediterránea de Comunicación, 2021)
The Spanish black cinema: from the Spanish noir to the present police one. It proposes a trip from the background of the Spanish black cinema - 1940s - to the present. The play, broken into 6 chapters - actually 8, although the last two are considered annexes with encyclopedic functions - goes chronologically through the evolution of the gender, making notes about his most relevant feature films and directors. The author guides us through comments and personal opinions, that are based in both critics from professionals of the time - Méndez Leite or Fernandez Santos - and declarations from the filmmakers themselves - from Rovira Beleta to Enrique Urbizu.